Pengaruh Kepemilikan Institusional, Capital Intensity, Dan Sales Growth Terhadap Tax Avoidance Pada Industri Barang Konsumsi Di BEI Periode 2017- 2023 - Gula, Valeria Eldyn; Maria Grasella Tunya; Katharina Yuneti (Jurnal Projemen UNIPA, 2025)
This study aims to examine the effect of each variable—Institutional Ownership, Capital Intensity, and Sales Growth—on Tax Avoidance in the Consumer Goods Industry listed on the Indonesia Stock Exchange. The data source for this research is the Indonesia Stock Exchange, covering the period from 2017 to 2023. Hypothesis testing was conducted using Panel Data Regression analysis with the Random Effect model. The results of this study indicate that there is no significant effect of Sales Growth on Tax Avoidance, whereas Institutional Ownership and Capital Intensity have a significant effect on Tax Avoidance.